A Win for The Market, A Loss for The State: Asean’s Property Debt Policy Reinterpreted - Luthpiyah Juliandara; Rianti Setyawasih; Isti Pujihastuti (Cakrawala Repositori IMWI)
Examining the influence of profitability, liquidity, and corporate asset structure as control variables on debt policy across five ASEAN countries, this study also investigated differences in debt policies among countries. A purposive sample of 264 companies (1,320 firm-year observations) was selected for the 2021–2025 period using data from LSEG/Refinitiv Workspace. The data were winsorized at the 1% and 99% levels and analyzed using panel data regression models, including the Common Effect Model, Fixed Effects Model, and Random Effects Model, with model selection conducted through the Chow and Hausman tests. The Fixed Effects Model (FEM) was selected as the primary model (F-pooled = 10.35; p < 0.001; Hausman ?² = 27.81; p < 0.001). Profitability had a negative effect on debt policy, which was significant in the Random Effects Model (REM) and marginally significant in the FEM. Asset structure showed inconsistent effects across models, while firm size consistently demonstrated a significant positive effect. Liquidity also produced inconsistent results across the models. No significant differences in debt policies were found among countries, either before or after controlling for firm size. Profitability and firm size emerged as relatively consistent determinants of debt policy, whereas the role of asset structure remained unstable across models and observation periods. Debt policies among ASEAN property sector companies did not differ significantly after accounting for firm size heterogeneity. This study extends previous research by expanding the scope of ASEAN property sector debt policy analysis from three to five countries and extending the observation period to 2025. Furthermore, it highlights the sensitivity of asset structure findings to the observation period and emphasizes the importance of controlling for firm size when interpreting cross-country differences in debt policy.